UNDERSTANDING PEACEBUILDING FUNDAMENTALS IN SOUTHEAST ASIA: Intersection among Religion, Education and Psychosocial Perspective - Taufiq, Imam; Makmun, Muhammad; Zuhri, Mishbah Khoiruddin; Sessiani, Lucky Ade; Safitri, Ririh Megah (AL-TAHRIR, 2022)
This study tries to present a study on Understanding the basics of peacebuilding in Southeast Asia by bringing together three approaches, namely religious, educational, and psychosocial approaches. The focus of this research is, first, to identify an overview of the fundamental values and basic principles of peacebuilding adopted by peacebuilding organizations in Southeast Asia. Second, to identify approaches adopted by peacebuilding organizations that reflect the intersection of religious, educational, and psychosocial perspectives to build peace in Southeast Asian societies. This study finds that first, Peace in Southeast Asia is influenced by values and basic principles of harmony and peace-building such as spirituality, local wisdom, brotherhood or togetherness, deliberation, tolerance, ikhlas (voluntary), and equality. This value is embraced by peace-building organizations in Southeast Asia on the basis that on the one hand, each religion teaches about unity, while on the other hand, the spirit of unity will also make a significant contribution in the national context.